2017
DOI: 10.1155/2017/9794053
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Shielding Characteristics of Eco-Friendly Foamed Concrete Wall

Abstract: The electromagnetic shielding characteristics according to the material composition of foamed concrete, which was manufactured to reduce environmental pollution and to economically apply it in actual building walls, were researched herein. Industrial byproducts such as ladle furnace slag (LFS), gypsum, and blast furnace slag (BFS) were added to manufacture foamed concrete with enhanced functionalities such as lightweight, heat insulation, and sound insulation. The electrical characteristics such as permittivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Hafiflik, ısı yalıtımı ve ses yalıtımı gibi gelişmiş işlevlere sahip köpüklü beton üretimi için pota fırını cürufu (LFS), alçıtaşı ve yüksek fırın cürufu (BFS) gibi endüstriyel yan ürünler eklenmiştir. Gerçekte üretilen köpüklü betonun elektromanyetik koruma özelliklerini ölçmek için boş alan ölçümü kullanılmıştır [47]. Başka bir çalışmada, çimentolu kompozit üretiminde farklı endüstriyel alanlardan sağlanan hacimlerde doğal kum değiştirilmiş ve bu malzemelerin elektromanyetik kalkanlama, soğurma yetenekleri ve dielektrik sabitleri incelenmiştir.…”
Section: Materyal Ve Metotunclassified
“…Hafiflik, ısı yalıtımı ve ses yalıtımı gibi gelişmiş işlevlere sahip köpüklü beton üretimi için pota fırını cürufu (LFS), alçıtaşı ve yüksek fırın cürufu (BFS) gibi endüstriyel yan ürünler eklenmiştir. Gerçekte üretilen köpüklü betonun elektromanyetik koruma özelliklerini ölçmek için boş alan ölçümü kullanılmıştır [47]. Başka bir çalışmada, çimentolu kompozit üretiminde farklı endüstriyel alanlardan sağlanan hacimlerde doğal kum değiştirilmiş ve bu malzemelerin elektromanyetik kalkanlama, soğurma yetenekleri ve dielektrik sabitleri incelenmiştir.…”
Section: Materyal Ve Metotunclassified
“…The increased electromagnetic wave reflection, scattering, and interference also contribute to the loss of electromagnetic wave energy [ 18 ]. Cho et al [ 19 ] reported that eco-friendly concrete absorbs more than 90 % of electromagnetic waves in the 4–8 GHz band when the foam content is low and the BFS content is high [ 20 ]. Anatol'evna et al found that electromagnetic activation can increase the surface area of solid components in foam concrete mixtures by 25 %–30 % [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Yen [3] studied the capacity of cement mortar to absorb EMR emitted by appliances in a confined living space. On the other hand, Cho et al [8] researched on EMR shielding effect of "eco-friendly foamed concrete wall". These studies intended to enhance penetration of EMR contrary to the present study that advocates shielding but, their results also indicate the material's defense ability against EMR.…”
Section: Introductionmentioning
confidence: 99%